Sex Differences in the Evolution of Neutralizing Antibodies to Severe Acute Respiratory Syndrome Coronavirus 2. (7th March 2021) - Grzelak, Ludivine; Velay, Aurélie; Madec, Yoann; Gallais, Floriane; Staropoli, Isabelle; Schmidt-Mutter, Catherine; Wendling, Marie-Josée; Meyer, Nicolas; Planchais, Cyril; Rey, David; Mouquet, Hugo; Reix, Nathalie; et al.
Abstract: We measured anti-spike (S), nucleoprotein (N), and neutralizing antibodies in sera from 308 healthcare workers with a positive reverse-transcription quantitative polymerase chain reaction result for severe acute respiratory syndrome coronavirus 2 and with mild disease, collected at 2 timepoints up to 6 months after symptom onset. At month 1, anti-S and -N antibody levels were higher in male participants aged >50 years and participants with a body mass index (BMI) >25 kg/m 2 . At months 3–6, anti-S and anti-N antibodies were detected in 99% and 59% of individuals, respectively. Anti-S antibodies and neutralizing antibodies declined faster in men than in women, independent of age and BMI, suggesting an association of sex with evolution of the humoral response. Abstract : We measured the levels of antibodies in 308 severe acute respiratory syndrome coronavirus 2–infected individuals, collected up to 6 months after symptom onset. Anti-spike antibodies and neutralizing antibodies declined faster in men than in women, suggesting an association of sex with evolution of the humoral response.